Cutting-edge biotechnological advancement in islet delivery using pancreatic and cellular approaches. - Elnashar, Magdy; Vaccarezza, Mauro; Al-Salami, Hani (2020)
There are approximately 1 billion prediabetic people worldwide, and the global cost for diabetes mellitus (DM) is estimated to be $825 billion. In regard to Type 1 DM, transplanting a whole pancreas or its islets has gained the attention of researchers in the last few decades. Recent studies showed that islet transplantation (ILT) containing insulin-producing β cells is the most notable advancement cure for Type 1 DM. However, this procedure has been hindered by shortage and lack of sufficient islet donors and the need for long-term immunosuppression of any potential graft rejection. The strategy of encapsulation may avoid the rejection of stem-cell-derived allogeneic islets or xenogeneic islets. This review article describes various biotechnology features in encapsulation-of-islet-cell therapy for humans, including the use of bile acids.